A taxonomic study of Quercus langbianensis complex based on morphology and DNA barcodes of classic and next generation sequences - Hoàng, Thị Bình (2023)
The taxonomy of Quercus langbianensis and its relatives in Vietnam and Cambodia have been revised based on evidence obtained from field observations, morphological comparison of herbarium specimens and molecular analyses using both classic and next generation DNA markers. Based on Bayesian inference using rbcL, matK and ITS regions and Neighbour-joining tree using genome-wide sequences amplified with multiplexed inter-simple sequence repeat (ISSR) primers (MIG-seq), the authors recognised ten species in the complex in Vietnam and Cambodia, three of which are newly described in this paper: Q. baolamensis sp. nov., Q. bidoupensis sp. nov. and Q. honbaensis sp. nov. These new species are all phenotypically similar to Q. langbianensis s. str. in having lanceolate to oblanceolate leaf shape, upper 4–5/6–serrated leaf margin, acute or acuminate leaf apex and bracts of cupule arranged in 5–9 rings but distinguished both morphologically and phylogenetically. In molecular phylogenetic reconstructions, Q. bidoupensis is not close to any other species. In the Bayesian tree, Q. honbaensis is sister to both Q. blaoensis and Q. camusiae that are found in the same locality but morphologically distinct and those three species are sister to Q. langbianensis s. str., while Quercus baolamensis is not sister to Q. langbianensis s. str. in both the Bayesian tree and MIG-seq tree. In addition, Q. cambodiensis and Q. baniensis previously reduced to Q. langbianensis s. lat. have been recognised as distinct species. Six species were in need of lectotypification and that is undertaken herein.